Multiplication Operator with BMO Symbols and Berezin Transform. (6th April 2015) - Feng, Xue; Zhang, Kan; Dong, Jianguo; Liu, Xianmin; Guan, Chi
Abstract : We discuss multiplication operator with a special symbol on the weighted Bergman space of the unit ball. We give the necessary and sufficient conditions for the compactness of multiplication operator on the weighted Bergman space of the unit ball.